Cydnocoris Stål, 1866 (Insecta: Heteroptera: Reduviidae): a junior synonym of Cutocoris Stål, 1859 - Swanson, Daniel R. (Zootaxa, 2019)
The purpose of this note is to review the usage of the generic names Cutocoris Stål, 1859 and Cydnocoris Stål, 1866 (type species: Myocoris gilvus Burmeister, 1838) for a genus of harpactorine assassin bugs from the Oriental Region, the latter being an unnecessary replacement name proposed for the former. Although Cutocoris Stål, 1859 has been used rarely since its replacement and Cydnocoris is undoubtedly in prevailing usage, it is demonstrated that neither name has been used extensively in the last century; thus, the case for suppression of Cutocoris Stål, 1859 lacks strong support. As a consequence, Cydnocoris Stål, 1866 is replaced by its senior synonym, Cutocoris Stål, 1859.